Modelling the influence of social network with a multiple group latent class analysis. Issue 2 (3rd April 2022) - Dey, Ankita; Mukherjee, Diganta; Sen Roy, Sugata
ABSTRACT: Presence of social network among the respondents in a survey may have an influence on the patterns of response. Latent class analysis identifies hidden subgroups in the respondents in a survey and simplifies the structure of heterogeneity amongst them. In the present study, a new model of social network-informed multiple group latent class analysis is developed by introducing a parameter measuring the influence of a social network on a respondent. For suitable application of the proposed model, data from 75 Indian villages with detailed demographic characteristics and a diverse social and economic network are used. The present study examined the methodological aspect of the proposed model of multiple group latent class analysis adjusted for the impact of social network.